Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

How do you solve 5h-6-h+10=12

Sagot :

Here's how to solve:

Simplifying 5h + -6 + -1h + 10 = 12 Reorder the terms: -6 + 10 + 5h + -1h = 12 Combine like terms: -6 + 10 = 4 4 + 5h + -1h = 12 Combine like terms: 5h + -1h = 4h 4 + 4h = 12 Solving 4 + 4h = 12 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 4h = 12 + -4 Combine like terms: 4 + -4 = 0 0 + 4h = 12 + -4 4h = 12 + -4 Combine like terms: 12 + -4 = 8 4h = 8 Divide each side by '4'. h = 2 Simplifying h = 2
5h-6-h+10=12
4h+4=12
4h+4-4=12-4
4h=8
h=2
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.